Primary Care Physician Supply for Missouri - Shaffer, Todd (Mo Med, 2016)
Primary Care Supply is not at a level to support needs for the U.S. public now or in the future. Missouri is deteriorating to an extreme shortage of primary care clinicians. With a present supply that is stagnant and not meeting patient needs, new opportunities to select and educate the next generation of physicians will be necessary to meet the predicted health care needs for our citizens. Examining the pipeline, process of medical education, practice transformation, and payment reform are important for the future.1 We should encourage our training institutions to provide resources for increasing the types of physicians we need for the next generation. Local and national leadership will need to heed the advice of forecasts and provide new methods and solutions for the needs of society. Academic institutions should be held to achieving a true output of physicians for the needs of society.